Affirmative action around the world: Insights from a new dataset (update) - Rachel M. Gisselquist; Min J. Kim; Simone Schotte; Chinmayi Srikanth (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Affirmative action, or positive discrimination favouring the members of marginalized populations, is a key policy approach to addressing group-based inequalities. It is adopted in dozens of countries around the world in the areas of, for instance, university enrolment, public employment, and political representation. Public debate over affirmative action is heated in many contexts, underscoring both potential benefits, such as correcting historical injustices, supporting marginalized groups, and promoting equality, and potential harms, especially in terms of perceptions of fairness and societal conflict. In order to better evaluate such claims and to consider the appropriateness of affirmative action policies across diverse contexts, further information about these policies is needed. Although there is a large research literature on affirmative action, much of it focuses on a limited number of countries. This paper introduces a new Affirmative Action Database which speaks to this research gap. It provides detailed information in a standardized format on the design and modalities of affirmative action policies, as well as on their adoption, implementation, associated controversies, and impact. The Affirmative Action Database thus can be used to provide a systematic description of policies and, together with other crosscountry databases, to situate and examine experiences of them comparatively, including within regional and global perspectives. Versions 1 and 2, discussed in this paper, cover 81 countries.
Keywords: I38; J5; J15; Z13; 330; affirmative action; positive action; horizontal inequality; ethnicity; race; social justice